Pengaruh Motivasi, Beban Kerja Dan Penilaian Kerja Yang Memiliki Dampak Pada Kepuasan Kerja Guru SMP Negeri 3 Lasem - Hasanah, Uswatun; Lukiarti, Ming Ming (Universitas Muhammadiyah Metro, 2023)
The purpose of this research activity is to prove and explain the impact of motivation variables,workload and work assessment on teacher job satisfaction at SMP Negeri 3 Lasem. The researchpopulation consisted of 34 teachers from the school, and saturation techniques were used to takesamples from the entire population. Data was collected through a questionnaire survey, and data wasanalyzed through multiple regression. This research obtained results where individual workloadvariables had no significant effect on job satisfaction, while individual motivation and workassessment variables had a significant effect on teacher satisfaction. The dependent variable of jobsatisfaction of 93.6% can be explained by three independent variables: motivation, workload, andwork assessment. Other variables outside the research accounted for 6.4% of the dependent variablejob satisfaction.